In-Vitro antidiabetic potential of Piliostigma thonningii leaf column chromatographic fractions - Ukwuani-Kwaja, Angela Nnenna; Suru, Ibrahim Mohammad; Nwaogu, Jude; Sani, Ibrahim (Journal of Medicinal Herbs and Ethnomedicine, 2023)
Diabetes mellitus is a metabolic disease characterized by high blood sugar that profoundly affects human health and economy. Although there are a plethora of antidiabetic drugs in the market, the efficacy shown by some medicinal plants sometimes outperforms that of synthetic drugs while being more affordable and less toxic. This study was conducted to evaluate the anti-diabetic potential of column-chromatographic fractions of Piliostigma thonningii leaf. Phytochemical screening, column, and thin layer chromatography were respectively conducted following standard laboratory protocols. The in-vitro antidiabetic activity of the extracts was assessed using alpha-glucosidase and hemoglobin glycosylation inhibitory methods. A total of 175 column fractions (CF1-CF175) were eluted respectively. Thin layer chromatography protocols employed pooled a total of 11 (A-J) fractions. The result showed significant (P>0.05) inhibition of alpha-glucosidase in only fraction J2, which was significantly greater when compared to standard drug (Voglibose) and crude extract. Also, there was no significant hemoglobin glycosylation inhibitory effect in all fractions compared with crude extract and standard drugs (Voglibose). In conclusion, P. thonningii leaf exhibited alpha-glucosidase and hemoglobin glycosylation inhibitory potentials that further support its usage as a hypoglycemic agent.